Pengembangan Manajemen Sumber Daya Serta Manajemen Kinerja Dalam Meningkatkan Fungsi Kualitas Sumber Daya Manusia: Suatu Kajian Literatur - Edi Irawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This article aims to review and attempt to confirm the concept of development of resource management and performance management in improving the quality function of human resources. The research method used is qualitative and literature studies or library research. Based on the results and discussion, it can be concluded that for the development of human resources and performance management in improving the quality function of human resources based on the concept, it can be done through: (a) Management training and development, (b) Identification of training and development needs, (c) Benefits, Training and development objectives, (d) Training Methods, (e) Benefits of performance management and (f) Performance measurement,(g) Performance management objectives.